2011
DOI: 10.1186/1748-717x-6-46
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of thyroid associated ophthalmopathy treated by radiation therapy

Abstract: Thyroid associated orbitopathy is a common manifestation of Graves disease. Many options can be considered for treatment. In this case series, we reviewed the medical records of 17 patients who received radiation therapy (RT) for GO in a tertiary care center between 1997 and 2007. All patients received 20 Gy to both orbits and 12 of them (71%) had already received one or more trials of steroid therapy prior to RT. After a median follow-up of 2 years, a subjective improvement in exophthalmos and vision was repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
10
1
2
Order By: Relevance
“…1 It is the most frequent orbital disorder and is the most common cause of unilateral and bilateral proptosis in adults. [2][3][4] Internationally, it is detectable in approximately 10 to 60% of GD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is the most frequent orbital disorder and is the most common cause of unilateral and bilateral proptosis in adults. [2][3][4] Internationally, it is detectable in approximately 10 to 60% of GD patients.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 Smokers are estimated to represent 64% of patients with GD and GO. 9 The risk of GO is found to be related to active smoking and is proportional to the number of cigarettes smoked per day.…”
Section: Introductionmentioning
confidence: 99%
“…Dopiero później rozpoczęto napromienianie oczodołu jako pierwotnego miejsca, w którym toczy się proces patologiczny. Pierwszym urządzeniem zastosowanym do radioterapii był aparat ortowoltowy, następnie zastąpiony przez akcelerator liniowy [23,24].…”
Section: Prace Poglądoweunclassified
“…Later, radiation was correctly applied to the orbital tissue. Firstly, the orthovoltage machine was used, than a linear accelerator was adapted [23,24].…”
Section: Orbital Radiotherapy -Basic Informationmentioning
confidence: 99%
“…Abboud et al [31] reviewed 17 patients and found 65% responded favorably to radiotherapy alone whereas 87-97% responded when radiotherapy was combined with steroids. Abboud et al [31] reviewed 17 patients and found 65% responded favorably to radiotherapy alone whereas 87-97% responded when radiotherapy was combined with steroids.…”
Section: Efficacy Of Radiotherapymentioning
confidence: 99%